2021
DOI: 10.1002/ehf2.13513
|View full text |Cite
|
Sign up to set email alerts
|

WBC count predicts heart failure in diabetes and coronary artery disease patients: a retrospective cohort study

Abstract: Aims White blood cell (WBC) count in healthy people is associated with the risk of coronary artery disease (CAD) and mortality. This study aimed to determine whether WBC count predicts heart failure (HF) requiring hospitalization as well as all-cause death, acute myocardial infarction (AMI) and stroke in patients with Type 2 diabetes mellitus and established CAD. Methods We conducted this retrospective registry study that enrolled consecutive patients with Type 2 diabetes mellitus and CAD based on coronary art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…45,46 In addition, in patients with type 2 diabetes and coronary heart disease, higher WBC counts are predictors of atrial fibrillation, all-cause death, and hospitalization for acute myocardial infarction. 47 In the present study, we demonstrated that elevated WBC counts are an independent risk factor of i-IGT. The elevated WBC counts in patients with i-IGT further suggest a role for chronic inflammation in the progression of i-IGT.…”
Section: Discussionsupporting
confidence: 62%
“…45,46 In addition, in patients with type 2 diabetes and coronary heart disease, higher WBC counts are predictors of atrial fibrillation, all-cause death, and hospitalization for acute myocardial infarction. 47 In the present study, we demonstrated that elevated WBC counts are an independent risk factor of i-IGT. The elevated WBC counts in patients with i-IGT further suggest a role for chronic inflammation in the progression of i-IGT.…”
Section: Discussionsupporting
confidence: 62%
“…CRP and FIB are acute-phase reactants induced by inflammatory cytokines and exert proinflammatory effects on the vascular endothelium to promote thrombotic states ( 8 , 9 ). Another accessible inflammatory marker, WBC, is an independent predictor of hospitalization for heart failure, acute myocardial infarction, and all-cause death in patients with CAD ( 10 ). A low-grade inflammation (INFLA) score, which comprises hs-CRP, WBC, platelet count, and granulocyte-to-lymphocyte ratio ( 11 ), has been used in the Moli-sani cohort and is independently associated with adverse health risks, particularly in individuals with diabetes and cardiovascular disease (CVD) ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…HF events were reported to the study office and subsequently adjudicated by the event evaluation committee. 14 …”
Section: Methodsmentioning
confidence: 99%
“…HF in our study was principally diagnosed according to the diagnostic criteria of the Framingham Heart Study13 and based on information on medical records, that is, response to treatments with diuretics and vasodilators. HF events were reported to the study office and subsequently adjudicated by the event evaluation committee 14…”
Section: Methodsmentioning
confidence: 99%